Factors influencing the intentions to major in accountancy. - Ong, Lih Chin. (2008)
This study uses the Theory of Reasoned Action (TRA) model to determine if differences exist between students with accounting intentions and students with non-accounting intentions. TRA is also used to investigate the extent to which gender influences the accounting intentions of students.